BELANJA ONLINE GEN Z: DITINJAU DARI DAYA TARIK IKLAN DAN CELEBRITY ENDORSER - Lestari, Fitri Dwi; Setiadarma, Dani (Mediakom : Jurnal Ilmu Komunikasi, 2024)
Communication in marketing is an important aspect for the successful growth of a company. Marketing communication is an attempt to convey messages to the public, especially target consumers, regarding the existence of products in the market. Marketing communication activities can be carried out by salespeople, advertising, personal selling, or sales through various media, conventional media and new media. Marketing communication in the end is to encourage consumers to finally make a purchase decision. Purchase intention is mediated by one of the variables, namely, buying interest. Many factors influence consumer purchase intention, including advertising attraction, e-wom, brand ambassador, celebrity endorser, brand image, brand awareness, advertising exposure, and others. The purpose of this study was to determine the effect of the advertising appeal and celebrity endorsers on purchase intention. The sample in this study was 170 respondents. The sampling technique was carried out by purposive sampling technique where the researcher determined the criteria for the research respondents themselves. Data collection was carried out using a questionnaire with measurements using a Likert scale, then processed using a statistical program. There is an effect of the advertising appeal and celebrity endorsers on purchase intention in e-commerce in Generation Z simultaneously or partially. The influence of the advertising appeal and celebrity endorsers on purchase intention in this study is significant and positive, which means that the higher the value of the two independent variables, the higher the purchase intention will be. Based on the results of hypothesis testing, it is proven that H1, H2, and H3 are accepted.